APPLICATION OF VALUE ENGINEERING IN PROJECT ROAD MAINTENANCE ACTIVITY AT THE PUBLIC WORKS DEPARTMENT OF SPATIAL PLANNING IN GROBOGAN - Hari Budi Prasetyo; Rachmat Mudiyono (UNISSULA Semarang, 2018)
One of the most frequent tasks of Public Works and Spatial Planning (PUPR) of Grobogan Regency is the handling of road damage with routine road maintenance. Implementation of material procurement is done contractually with provider of goods / services while for the implementation of activities in the field implemented by UPTD area according to location of activity. So in the implementation of road maintenance activities PUPR Service Grobogan District requires a method of engineering value or commonly called Value Engineering in order to be implemented efficiently and optimally. The purpose of this study is to determine the cost efficiency in the implementation of road maintenance; know the cost components that have the potential to be saved / streamlined in the implementation of road maintenance and also to know the extent to which this value engineering can be applied to the implementation of road maintenance on a self-managed basis. The method used is descriptive qualitative with analytical technique using value engineering to answer the background of problem and purpose. The results of this study indicate that contractual road maintenance is cheaper because it does not rent equipment but has a short plan life of maximum 3 years. While road maintenance is done by self-managed has a plan life of up to 5 years. The cost of renting equipment is a very possible component to save. Value engineering also yields a final conclusion that road maintenance work carried out with self-managed systems has a short and efficient procedure; better road quality and faster processing times compared to conventional systems. Keywords: Grobogan District; Road Maintenance; Value Engineering.